High-fat diet exposure, regardless of induction of obesity, is associated with altered expression of genes critical to normal ovulatory function. (15th July 2018) - Hohos, Natalie M.; Cho, Kirstin J.; Swindle, Delaney C.; Skaznik-Wikiel, Malgorzata E.
Abstract: We evaluated the impact of high-fat diet (HFD) on ovarian gene expression. Female 5-week-old C57BL/6J mice were fed a 60% HFD or standard chow for 10 weeks. HFD-fed mice were then separated into obese (HF-Ob) and lean (HF-Ln) based on body weight. HFD exposure led to impairment of the estrous cycle, changes in hormones affecting reproduction, and decreased primordial follicles regardless of the development of obesity. RNA-sequencing of whole ovaries identified multiple genes with altered expression after HFD, with 25 genes displaying decreased expression in both HF-Ln and HF-Ob mice compared to the chow-fed controls (q < 0.05). Several of these 25 genes are involved in normal ovarian functions, including ovulation ( Edn2, Tnfaip6, Errfi1, Prkg2, and Nfil3 ), luteinization ( Edn2 ), and luteolysis ( Nr4a1 ). Taken together, elevated dietary fat intake, regardless of obesity, is associated with impaired estrous cycle, depletion of the ovarian reserve, and altered expression of genes critical to normal ovulatory function. Highlights: HFD alters the expression of ovarian genes involved in normal ovulatory function, irrespective of obesity. HFD negatively impacts ovarian reserve. HFD is associated with estrous cycle disruption - finding suggestive of an abnormal ovulatory function.